No Evidence of a Dichotomy in the Elliptical Galaxy Population - Rogério Monteiro-Oliveira; Yen-Ting Lin; Wei-Huai Chen; Chen-Yu Chuang; Abdurro’uf; Po-Feng Wu (The Astrophysical Journal, 2025)
The advent of large integral field spectroscopic surveys has found that elliptical galaxies (EGs) can be divided into two classes: the fast rotators (whose kinematics are dominated by rotation) and the slow rotators (which exhibit slow or no rotation pattern). It is often suggested that while the slow rotators typically have boxy isophotal shapes, have a high α -to-iron abundance ratio, and are quite massive, the fast rotators often exhibit the opposite properties (that is, having disky isophotes, lower α -to-iron ratio, and of typical masses). Whether the EGs consist of two distinct populations (i.e., a dichotomy exists) remains an unsolved issue. To examine the existence of the dichotomy, we used a sample of 1895 EGs from the SDSS-IV MaNGA survey and measured robustly the stellar kinematics, isophotal shapes, and [Mg/Fe] ratio. We confirmed the previous finding that the bulk of the EGs are disky (65%) and fast rotators (67%), but we found no evidence supporting a dichotomy, based on a principal component analysis. The different classes (boxy/disky and slow/fast rotators) of EGs occupy slightly different loci in the principal component space. This may explain the observed trends that led to the premature support of a dichotomy based on small samples of galaxies.